Revealing Gender Inequality in Selection of Topics for Comments on Infidelity in Gossip Channel - Dewinda, Viona Musti; Hamzah, Hamzah (Universitas Negeri Padang, 2024)
This research aimed to employ Van Dijk's Ideological Square to examine gender inequality in infidelity news comments on YouTube. The study used a qualitative research technique. According to the results, the most popular netizen comments concerned for Virgound and Syahnaz were